Workshop on Bean Varietal Improvement in Africa (1989, Maseru, Lesotho). Proceedings - Smithson, James Brady (Southern Africa Development Coordination Conference (SADCC), 1989)
Information is presented on the activities of the pan African bean research network. Reports, presented by country, highlight bean production constraints and the status, methods, and future needs of var. breeding. Evaluation of genetic resources, selection of segregating populations, establishment of regional nurseries, and production of basic seed and var. release are discussed as key issues in implementing future strategies in the region. (CIAT)